Who owns this data? using dialogic reflection to examine an ethically important moment. Issue 3 (4th May 2019) - McDonough, Sharon; Brandenburg, Robyn
ABSTRACT: There has been growing use of reflective practice as a means for examining ethically important moments that occur during research. Reflective practice enables researchers to be alert to the unfolding of these ethically important moments and to consider how they will respond to them. In this paper, we use dialogic reflection to explore an ethically important moment that occurred during one of our research projects. We present our dialogic reflective conversation as a means of exploring the ethical issues associated with data ownership. We draw on this conversation to describe a framework for dialogic reflection that provides researchers with a process for engaging in reflection on their practice as ethical researchers.